(3eNJUQ EbJHGS GdCfhGQ hEdJeGS GdCRgGQ aj CfSGH GdUMGHI hQhGI GdBKGQs - (3CHi eMeO YHO Gddg Hf YHO GdQMef Hf YHO Gddg GdETHjdis; (3YHO Gddg Hf Ydj Hf YHO Gddg GddNej GdCfOdSj, CHh eMeO , GdQTGWj,J (B542 (3g` s
(3ChdgG (B:s
(3jHOC ef MQa Gdeje HGSe (B: (3GdeGRfi s
(3BNQgG (B:s
(3hjfJgi Edi GSe (B: (3GdSeGfi hGdjefi s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B105 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B262s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B133 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B134s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs